PENGARUH PEMBERIAN EDUKASI TERHADAP PERILAKU PENCEGAHAN STUNTING PADA IBU HAMIL TM I DI WILAYAH KERJA PUSKESMAS LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Arpen, Ratih Septiana; Silvia, Elwitri; Asmawati, Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : Stunting is defined as impaired growth and development of children due to chronic malnutrition during the first thousand days of life. Stunting affects a child's height and can have adverse effects on cognitive development and long-term health. The purpose of this study was to determine the effect of providing education on stunting prevention behavior in pregnant women in the Lubuk Alung Puskesmas Working Area. This research method uses One Group Pretest-Posttest de-edesign, this research will be carried out in December- January 2025 in the working area of the Lubuk Alung Health Center. The population of this study is 27 TM 1 pregnant women. The data in this study was processed using the paired sample t test. Data was collected using questionnaire sheets, Data analysis was carried out univariate and bivariate using paired sample t test. The results showed that the average score of pregnant women's behavior before being given Stunting Prevention Education was <50 and after being given showed an increase in behavior with a score of >50. Based on the results of statistical tests there is an influence before and after being given education is Pvalue = 0.000 (<0.05) The conclusion of this study shows that there is an effect of providing education using leaflets and ppt on the behavior of preventing stunting in pregnant women tm 1 in the working area of the lubuk alung health center. It is recommended for pregnant women to be more active in following the routine examination program suggested by medical personnel and optimizing their healthKeywords: Stunting, Education, Pregnant Women TM I.